2018
DOI: 10.3390/met8020134
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effect of Mo and Cr on Microstructure and Mechanical Properties in NbV-Microalloyed Bainitic Steels

Abstract: Steel product markets require the rolled stock with further increasing mechanical properties and simultaneously decreasing price. The steel cost can be reduced via decreasing the microalloying elements contents, although this decrease may undermine the mechanical properties. Multi-element microalloying with minor additions is the route to optimise steel composition and keep the properties high. However, this requires deep understanding of mutual effects of elements on each other's performance with respect to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 78 publications
2
11
0
Order By: Relevance
“…Recent studies have shown that the improvement of tensile properties can also be achieved through the deformation in the austenite temperature region followed by accelerated cooling and warm deformation in the ferrite temperature region, leading to finer microstructures [38]. In addition, the microalloying with niobium, vanadium and molybdenum can also improve the tensile strength via precipitation and solid solution strengthening [39,40]. Thus, further research on the enhancement of tensile properties in DP and TRIP steels produced by the modified strip casting can be dedicated to the investigation of effects of thermo-mechanical control process and alloying.…”
Section: Tensile Propertiesmentioning
confidence: 99%
“…Recent studies have shown that the improvement of tensile properties can also be achieved through the deformation in the austenite temperature region followed by accelerated cooling and warm deformation in the ferrite temperature region, leading to finer microstructures [38]. In addition, the microalloying with niobium, vanadium and molybdenum can also improve the tensile strength via precipitation and solid solution strengthening [39,40]. Thus, further research on the enhancement of tensile properties in DP and TRIP steels produced by the modified strip casting can be dedicated to the investigation of effects of thermo-mechanical control process and alloying.…”
Section: Tensile Propertiesmentioning
confidence: 99%
“…The present Special Issue on Advances in Microalloyed Steels includes two review papers [1,2] and nine research papers [3][4][5][6][7][8][9][10][11]. In all of them, different combinations of microalloying elements are analyzed in terms of process, microstructure, and mechanical property modification.…”
Section: Contributionsmentioning
confidence: 99%
“…The alternatives in microalloying are clearly reflected in terms of the grades studied in the different papers. Nb is present in many of them [1,2,5,7,8,10,11], alone or in combination with Mo [2,5,10], Ti [8], and V [10]. Two papers deal with Ti-Mo combinations [6,9], and the last two articles analyze the addition of V [4] and Al [3] as microalloying elements.…”
Section: Contributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…From various experiments on methods to improve the mechanical properties of lateritic steel, austempering heat treatment, and alloying elements were chosen because they can form bainite microstructures with complex characteristics with optimal energy absorption capabilities. In previous research, the addition of Mo and Cr to is well known as element which provide phase balance strengthening by facilitating the formation of bainit structure, and solid solution strengthening [10][11]. Furthermore, in several studies have reported that austempering process which leads to bainitic or mixed bainite-martensite microstructures provides a better combination of mechanical properties, especially strength and impact toughness [12].…”
Section: Introductionmentioning
confidence: 99%